Overview of Experimental Investigation of X-ray TransitionRadiation Generated by 300-900 MeV Electrons in PeriodicMultifoil Radiators - Kuznetsov S. I. Sergey Ivanovich; Kaplin V. V. Valeriy Viktorovich; Uglov S. R. Sergey Romanovich; Zabaev V. N. Viktor Nikolaevich (2013, 2013)
Title screen.